Case Report: Multidrug-resistant Tuberculosis (MDR TB) - Aswita Damayanti; Alfi Raudatil Jannah (Faculty of Medicine, Public Health, and Nursing, 2018)
...................... The patient lived with her husband, her three children, and a very old mother-in-law. The patient was the first child of 2 siblings with a history of spontaneous birth and was assisted by a birth attendant with cry spontaneously. Her mother-in-law had the same history of the disease, i.e., the first category of pulmonary TB. Her mother-in-law was treated at the primary health care facility for six months and was declared cured by the primary health care facility ten years ago. Her sister-in-law also suffered from the third category of pulmonary TB and did not regularly take the medication, and she died two years ago. The patients have a history of miscarriage once, which was during her fourth pregnancy. Her mother and father were Javanese. The patient's husband worked as a laborer on a coconut farm. So, the income was uncertain every day. The patient came from the lower socio-economic class, so the patient had health insurance for low-income people or JAMKESMAS (Health Coverage). The patient's social relationship with the community was not good because the neighborhood marginally ostracized the patient's family due to her family history which suffered from pulmonary tuberculosis........................